Specialty DihydrobenzoxanthoneÃ¢â¬â¢s Artocarpus Purified By Vacuum Liquid Chromatography (VLC) - Aliefman Hakim (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
One family of plants that are source of bioactive chemicals is the Moraceae.Artocarpus is the main genus of the Moraceae. Several species of the genus Artocarpus have been isolated their secondary metabolites. The main fractions obtained from the VLC are analyzed again by TLC. Fractions that have same spots (Rf) pooled. Purification process on main factions are done repeatedly by radial chromatography. Flavonoid is the most found from Artocarpus plant. Dihydrobenzoxanthone is one of flavonoid derivatives which is successfully isolated from Artocarpus. Dihydrobenzoxanthone is only formed from the flavone with ring B which isoxygenated with pattern of 2', 4' and 5'. Students can be learned dihydrobenzoxanthoneÃ¢â¬â¢s Artocarpus by laboratory activities.ÃÂ